DAMPAK PEMBERIAN KREDIT UMUM PEDESAAN PT. BRI TERHADAP EKONOMI MASYARAKAT DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Shorea Khaswarina (Jurnal Ilmiah Pertanian, 2017)
Lending is expected to boost the economy. Through this study, researchers wanted to see the impact of granting Kupedes PT. Bank Rakyat Indonesia to economic masyaraka in Kampar District Kampar Kiri. Whether the credit has been used well in accordance with the intended purposes or otherwise. The method used is a survey method. The study was conducted to 30 people Kupedes debtor. Based on the results achieved show that credit had a positive impact on the local economy, in which the positive impacts vary bada on each loan amount. The greater the amount of the loan, the more bazaar impacts.